2017
DOI: 10.1073/pnas.1620993114
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic transcription factor SOX9 drives breast cancer endocrine resistance

Abstract: The estrogen receptor (ER) drives the growth of most luminal breast cancers and is the primary target of endocrine therapy. Although ER blockade with drugs such as tamoxifen is very effective, a major clinical limitation is the development of endocrine resistance especially in the setting of metastatic disease. Preclinical and clinical observations suggest that even following the development of endocrine resistance, ER signaling continues to exert a pivotal role in tumor progression in the majority of cases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 83 publications
8
67
0
Order By: Relevance
“…We found that ADHFE1 upregulates intracellular D-2HG under hypoxic conditions, reaching a 5-to 15-fold increase over baseline in cell culture experiments, providing a potentially new mechanism of D-2HG accumulation in breast cancer. We also observed that L-2HG increased in breast epithelial cells that were cultured under hypoxia (data state that promotes metastasis-seeding abilities, Wnt signaling, and breast cancer endocrine resistance (33)(34)(35). ADHFE1 may also affect the DNA methylation state of cells, as 2HG is an inhibitor of 5-methylcytosine hydroxylases (36).…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 68%
“…We found that ADHFE1 upregulates intracellular D-2HG under hypoxic conditions, reaching a 5-to 15-fold increase over baseline in cell culture experiments, providing a potentially new mechanism of D-2HG accumulation in breast cancer. We also observed that L-2HG increased in breast epithelial cells that were cultured under hypoxia (data state that promotes metastasis-seeding abilities, Wnt signaling, and breast cancer endocrine resistance (33)(34)(35). ADHFE1 may also affect the DNA methylation state of cells, as 2HG is an inhibitor of 5-methylcytosine hydroxylases (36).…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 68%
“…SOX9 also contributes to the maintenance of stem/progenitor cells in the liver, pancreas, and hair follicles (Furuyama et al, 2011, Vidal et al, 2005). Consequently, dysregulated SOX9 expression has been linked to the initiation and growth of a wide range of tumors: it has been shown to enhance proliferation and migration of prostate cancer cells and the formation of pancreatic ductal adenocarcinomas and is also implicated in metastasis and endocrine resistance in breast cancer (Deng et al, 2015, Jeselsohn et al, 2017). In murine BCCs, SOX9 was recently shown to be required for tumor initiation in a Wnt/β-catenin-dependent manner (Larsimont et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIRM1 SOX9 is a stem cell factor involved in tamoxifen resistant BCa (Jeselsohn, et al 2017). HOTAIR and BCL2 expression were correlated in breast tumors and HOTAIR was shown to act as a ceRNA by base-pairing with miR-206, thus relieving mIR-206's repression of BCL2 expression (Ding, et al 2017).…”
Section: Lncrnas In Breast Tumorsmentioning
confidence: 99%